2009
DOI: 10.1002/oa.1075
|View full text |Cite
|
Sign up to set email alerts
|

A supernumerary permanent mandibular premolar of wild boar (Sus scrofa L.) from the early medieval Novgorod, Russia

Abstract: The aim of this study was to investigate a unique case of polydonty in wild boar from the early medieval Novgorod (second half of 11th century AD). The only preserved distal part of the right mandibular branch shows a rotated transitional permanent extra premolar between P 3 and P 4 . This abnormality has the potential to serve as a territorially-based indicator of past wild boar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The proportion of polydonty found in the present study was surprising given the fact that supernumerary dentition in the species exceeds the primitive eutherian number (Thenius, 1989). Horwitz and Davidiovitz (1992) and Zinoviev (2010) reported such findings in archaeological material and Konjevic et al (2006) reported a supernumerary C1 in one male wild boar from Croatia. Many theories claim that supernumerary teeth may be of congenital origin and result from development of excess dental lamina, which may lead to the formation of additional tooth germs (Neville et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…The proportion of polydonty found in the present study was surprising given the fact that supernumerary dentition in the species exceeds the primitive eutherian number (Thenius, 1989). Horwitz and Davidiovitz (1992) and Zinoviev (2010) reported such findings in archaeological material and Konjevic et al (2006) reported a supernumerary C1 in one male wild boar from Croatia. Many theories claim that supernumerary teeth may be of congenital origin and result from development of excess dental lamina, which may lead to the formation of additional tooth germs (Neville et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…The other case of supernumerary mandibular premolar similar to that from Arlanpe was recently reported by Zinoviev () on a medieval wild boar from Novgorod (Russia). It displays a supernumerary premolar rotated ca .…”
Section: Discussionmentioning
confidence: 97%
“…We have found in the literature another two cases of a supernumerary premolar located between the P 3 and P 4 (Natsume et al ., ; Zinoviev, ). In both cases, the authors suggest that the supernumerary premolars display transitional morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations